2019
DOI: 10.1523/jneurosci.0588-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Correlates of Attention to Auditory Features

Abstract: Pitch and timbre are two primary features of auditory perception that are generally considered independent. However, an increase in pitch (produced by a change in fundamental frequency) can be confused with an increase in brightness (an attribute of timbre related to spectral centroid) and vice versa. Previous work indicates that pitch and timbre are processed in overlapping regions of the auditory cortex, but are separable to some extent via multivoxel pattern analysis. Here, we tested whether attention to on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…Under another interpretation, however, this effect could be seen as further evidence that brightness and pitch are closely related; in fact, pitch and timbre cues are known to interact perceptually (Allen & Oxenham, 2014;Marozeau & de Cheveigné, 2007;Melara & Marks, 1990;Warrier & Zatorre, 2002), and they may activate overlapping brain regions (Allen et al, 2019(Allen et al, , 2017Bizley et al, 2009;Warren et al, 2005). Given these similarities, a deficit in pitch processing should lead to an impairment in brightness processing to the extent that these dimensions are perceived by shared mechanisms.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Under another interpretation, however, this effect could be seen as further evidence that brightness and pitch are closely related; in fact, pitch and timbre cues are known to interact perceptually (Allen & Oxenham, 2014;Marozeau & de Cheveigné, 2007;Melara & Marks, 1990;Warrier & Zatorre, 2002), and they may activate overlapping brain regions (Allen et al, 2019(Allen et al, , 2017Bizley et al, 2009;Warren et al, 2005). Given these similarities, a deficit in pitch processing should lead to an impairment in brightness processing to the extent that these dimensions are perceived by shared mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…All three of these dimensions are known to interact perceptually (Allen & Oxenham, 2014;Marozeau & de Cheveigné, 2007;Melara & Marks, 1990;Verschuure & van Meeteren, 1975;Warrier & Zatorre, 2002), with pitch and brightness perception perhaps relying on overlapping neural mechanisms (Allen, Burton, Mesik, Olman, & Oxenham, 2019;Allen, Burton, Olman, & Oxenham, 2017;Bizley, Walker, Silverman, King, & Schnupp, 2009;Warren, Jennings, & Griffiths, 2005). Specifically, changes in pitch and brightness seem to activate strongly overlapping regions of auditory cortex, but produce patterns of activation within those regions that can be statistically distinguished (Allen et al, 2019(Allen et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adults often have difficulty distinguishing between pitch and the aspect of timbre known as brightness, describing increases in both as being "higher." In studies of discrimination, interference between the two dimensions is common (Allen & Oxenham, 2014;Borchert, Micheyl, & Oxenham, 2011;Lau & Werner, 2014), and in functional imaging studies, substantial overlap between representations of pitch and brightness has been reported (Allen, Burton, Mesik, Olman, & Oxenham, 2019). Musical training typically leads to be better pitch discrimination prior to explicit training (Madsen, Marschall, Dau, & Oxenham, 2019;Micheyl et al, 2006), but does not eliminate such interference (Allen & Oxenham, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, in spite of centuries of intense scrutiny, the precise nature of the auditory cues determining pitch in the general case has remained elusive, with many additional candidates beyond periodicity [3][4][5]. Moreover, in the perceptual domain, the independence of pitch from other perceptual attributes such as timbre has been recently challenged [6][7][8][9][10]. Here, we explore a unifying hypothesis, suggesting that a salient perceptual dimension on which sounds can be ordered from "low" to "high" is in fact a compound construct, seamlessly derived by listeners from the combination of distinct auditory cues, each adaptively weighted in a manner that can be sound-dependent and listener-specific.…”
Section: Introductionmentioning
confidence: 99%